Semi‐Natural Habitats Buffer the Effects of Crop Diversification on Arthropod Pest Control Services in Agricultural Landscapes - Thomas Perrot; Léa Beaumelle; Eva Thomine; Yann Tricault; Nicolas Desneux; Matthias Albrecht; Péter Batáry; Felix Bianchi; Klaus Birkhofer; Aliette Bosem Baillod; Rebecca Chaplin‐Kramer; Anne‐Marie Cortesero; et al. (Ecology Letters, 2026)
Crop diversification is a promising strategy to strengthen pest control services in agricultural landscapes. Diversifying crops may limit pests through host crop dilution or by enhancing top‐down control by their enemies. However, crop diversification may also benefit generalist pests through higher resource continuity. Using a large‐scale dataset encompassing 742 landscapes across 13 countries, we assessed the impact of landscape‐scale crop diversity on the abundance of natural enemies, the potential for biological control, and insect pest abundance. Crop diversification did not increase the overall abundance of natural enemies or the potential for biological pest control. Instead, crop diversity primarily favoured the abundance of specialist natural enemies and pests in highly simplified landscapes, an effect that was reduced in landscapes with high proportions of semi‐natural habitats. Lastly, low proportions of host crops in the landscape were associated with higher abundances of natural enemies. Taken together, our results indicate that crop diversification is not a ‘one size fits all’ strategy to control agricultural pests, and that other landscape characteristics, such as high amounts of semi‐natural habitats, must be considered to enhance biological pest control services.

From simulation to sustainability: using forest growth models for indicator-based bioeconomy monitoring - Mirjam Pfeiffer; Rüdiger Grote; Joachim Rock; Mart-Jan Schelhaas; Andreas Huth; Sara Filipek; Christopher P. O. Reyer; Boris Sakschewski; Sarah Bereswill; Mats Nieberg; Jessica Hetzer; Tim Anders; et al. (Regional Environmental Change, 2026)

Decoding corporate climate transition plans: A comparative analysis of 14 frameworks - Astrid B. Nicolajsen; Anders Bjørn; Tim C. McAloone; Daniela C.A. Pigosso (Journal of Environmental Management, 2025)

A simple climate-driven semi-mechanistic vegetation model can explain the pan-Asian extent of the glacial mammoth steppe - Lisa Merkens; Tim Anders; Wolfgang Traylor; Hervé Bocherens; Thomas Hickler (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Modelling past and future impacts of droughts on tree mortality and carbon storage in Norway spruce stands in Germany - Tim Anders; Jessica Hetzer; Nikolai Knapp; Matthew Forrest; Liam Langan; Merja Helena Tölle; Nicole Wellbrock; Thomas Hickler (Ecological Modelling, 2025)

Gross pathology and liver mercury concentrations in harbour porpoises, harbour seals and grey seals in Denmark, Northern Europe - Christian Sonne; Aage K.O. Alstrup; Sussie Pagh; Charlotte Bie Thøstesen; Trine Hammer Jensen; Tim Kåre Jensen; Anders Galatius; Line Kyhn; Jens Søndergaard; Ursula Siebert; Jan Lakemeyer; Rune Dietz (Science of The Total Environment, 2024)

Health risks from exposure to chemicals in clothing - Non-regulated halogenated aromatic compounds - Josefine Carlsson; Awat Dostberg; Tim Åström; Julia Matyjasiak; Anders Kallin; Sanja Juric; Ulrika Nilsson (Chemosphere, 2024)

Force capacity of trunk muscle extension and flexion in healthy inactive, endurance and strength-trained subjects—a pilot study - Tim Schönau; Christoph Anders (German Journal of Exercise and Sport Research, 2024)
Recreational sports are becoming increasingly important in overcoming the drawbacks of our modern sedentary lifestyle. We wanted to know whether ambitious strength or endurance training has a systematic effect on the maximum strength capacity of the trunk muscles compared to no sport at all. We investigated two groups of physically active men who practised either endurance (ET; cycling and triathlon, n = 13) or strength training (ST; power lifting, n = 13), and a group of healthy physically inactive men (control [C], n = 12). Training intensity was at competition level in both active groups. All participants performed isometric maximum voluntary contractions in flexion and extension direction. Independent of force direction maximum torque levels were highest for the ST group ( p < 0.001 vs. ET and C), but after normalizing to the subject’s upper body weight these differences decreased, together with a drop in significance levels (extension: p < 0.01 vs. C; flexion: p < 0.05 vs. ET; p < 0.01 vs. C). With respect to the ratio between extension and flexion maximum forces due to the small group size no systematic differences could be detected between the groups, but effect sizes imply relevant effects (ET vs. ST: d = 0.588, ST vs C: d = −0.811). The results of this pilot study indicate that ST show higher functional force capacity values for flexion compared to the other groups. For extension, ST and ET did not differ. These results imply relevant differences for the extension to flexion force ratio.

Multimodal 3D Mouse Brain Atlas Framework with the Skull-Derived Coordinate System - Johanna Perens; Casper Gravesen Salinas; Urmas Roostalu; Jacob Lercke Skytte; Carsten Gundlach; Jacob Hecksher-Sørensen; Anders Bjorholm Dahl; Tim B. Dyrby (Neuroinformatics, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

An Optimized Mouse Brain Atlas for Automated Mapping and Quantification of Neuronal Activity Using iDISCO+ and Light Sheet Fluorescence Microscopy - Johanna Perens; Casper Gravesen Salinas; Jacob Lercke Skytte; Urmas Roostalu; Anders Bjorholm Dahl; Tim B. Dyrby; Franziska Wichern; Pernille Barkholt; Niels Vrang; Jacob Jelsing; Jacob Hecksher-Sørensen (Neuroinformatics, 2021)
In recent years, the combination of whole-brain immunolabelling, light sheet fluorescence microscopy (LSFM) and subsequent registration of data with a common reference atlas, has enabled 3D visualization and quantification of fluorescent markers or tracers in the adult mouse brain. Today, the common coordinate framework version 3 developed by the Allen’s Institute of Brain Science (AIBS CCFv3), is widely used as the standard brain atlas for registration of LSFM data. However, the AIBS CCFv3 is based on histological processing and imaging modalities different from those used for LSFM imaging and consequently, the data differ in both tissue contrast and morphology. To improve the accuracy and speed by which LSFM-imaged whole-brain data can be registered and quantified, we have created an optimized digital mouse brain atlas based on immunolabelled and solvent-cleared brains. Compared to the AIBS CCFv3 atlas, our atlas resulted in faster and more accurate mapping of neuronal activity as measured by c-Fos expression, especially in the hindbrain. We further demonstrated utility of the LSFM atlas by comparing whole-brain quantitative changes in c-Fos expression following acute administration of semaglutide in lean and diet-induced obese mice. In combination with an improved algorithm for c-Fos detection, the LSFM atlas enables unbiased and computationally efficient characterization of drug effects on whole-brain neuronal activity patterns. In conclusion, we established an optimized reference atlas for more precise mapping of fluorescent markers, including c-Fos, in mouse brains processed for LSFM.

Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean - Manon Clairbaux; William W. L. Cheung; Paul Mathewson; Warren Porter; Nicolas Courbin; Jérôme Fort; Hallvard Strøm; Børge Moe; Per Fauchald; Sebastien Descamps; Hálfdán Helgason; Vegard S. Bråthen; et al. (Global Change Biology, 2021)
We explored the implications of reaching the Paris Agreement Objective of limiting global warming to Alle alle , Fratercula arctica , Uria aalge , Uria lomvia and Rissa tridactyla ) using tracking data for ~1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a “no mitigation” scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Diel vertical migration, size distribution and photoprotection in zooplankton as response to UV‐A radiation - Mikael T. Ekvall; Samuel Hylander; Tim Walles; Xi Yang; Lars‐Anders Hansson (Limnology and Oceanography, 2015)
The transparency regulator hypothesis (TRH) proposes that ultraviolet radiation (UVR) is a main driving force behind diel vertical migration (DVM) of zooplankton in clearwater systems. While previous studies have mainly studied DVM in relation to the TRH on a spatial scale across systems we here focus on long‐term trends in a single system in order to assess if UVR explains observed patterns in DVM. We show that the strength of DVM in Daphnia is to a large extent explained by UVR and we demonstrate a tipping point at which the UVR intensity drastically affects the strength of DVM in Daphnia . In contrast, the strength of DVM could not be explained by the level of UVR among calanoid copepods. The amount of photoprotective compounds did not differ between zooplankton found at different depths indicating that zooplankton do not change their vertical position in relation to the amount of accumulated photoprotective compounds. In addition, we show that both Daphnia and calanoid copepods display patterns of size structured migration.

Microbial community structure and functioning in marine sediments associated with diffuse hydrothermal venting assessed by integrated meta‐omics - Tim Urich; Anders Lanzén; Runar Stokke; Rolf B. Pedersen; Christoph Bayer; Ingunn H. Thorseth; Christa Schleper; Ida H. Steen; Lise Øvreas (Environmental Microbiology, 2014)
Summary Deep‐sea hydrothermal vents are unique environments on E arth, as they host chemosynthetic ecosystems fuelled by geochemical energy with chemolithoautotrophic microorganisms at the basis of the food webs. Whereas discrete high‐temperature venting systems have been studied extensively, the microbiotas associated with low‐temperature diffuse venting are not well understood. We analysed the structure and functioning of microbial communities in two diffuse venting sediments from the J an M ayen vent fields in the N orwegian‐ G reenland S ea, applying an integrated ‘omics’ approach combining metatranscriptomics, metaproteomics and metagenomics. Polymerase chain reaction‐independent three‐domain community profiling showed that the two sediments hosted highly similar communities dominated by E psilonproteobacteria , D eltaproteobacteria and G ammaproteobacteria , besides ciliates, nematodes and various archaeal taxa. Active metabolic pathways were identified through transcripts and peptides, with genes of sulphur and methane oxidation, and carbon fixation pathways highly expressed, in addition to genes of aerobic and anaerobic (nitrate and sulphate) respiratory chains. High expression of chemotaxis and flagella genes reflected a lifestyle in a dynamic habitat rich in physico‐chemical gradients. The major metabolic pathways could be assigned to distinct taxonomic groups, thus enabling hypotheses about the function of the different prokaryotic and eukaryotic taxa. This study advances our understanding of the functioning of microbial communities in diffuse hydrothermal venting sediments.

Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study - Dominique S. Michaud; Jacques Izard; Zachary Rubin; Ingegerd Johansson; Elisabete Weiderpass; Anne Tjønneland; Anja Olsen; Kim Overvad; Marie Christine Boutron-Ruault; Françoise Clavel-Chapelon; Laure Dossus; Rudolf Kaaks; et al. (Cancer Causes & Control, 2013)

Grading of Parameters for Urban Tree Inventories by City Officials, Arborists, and Academics Using the Delphi Method - Johan Östberg; Tim Delshammar; Björn Wiström; Anders Busse Nielsen (Environmental Management, 2013)

Metatranscriptomics of the marine sponge Geodia barretti : tackling phylogeny and function of its microbial community - Regina Radax; Thomas Rattei; Anders Lanzen; Christoph Bayer; Hans Tore Rapp; Tim Urich; Christa Schleper (Environmental Microbiology, 2012)
Summary Geodia barretti is a marine cold‐water sponge harbouring high numbers of microorganisms. Significant rates of nitrification have been observed in this sponge, indicating a substantial contribution to nitrogen turnover in marine environments with high sponge cover. In order to get closer insights into the phylogeny and function of the active microbial community and the interaction with its host G. barretti , a metatranscriptomic approach was employed, using the simultaneous analysis of rRNA and mRNA. Of the 262 298 RNA‐tags obtained by pyrosequencing, 92% were assigned to ribosomal RNA (ribo‐tags). A total of 109 325 SSU rRNA ribo‐tags revealed a detailed picture of the community, dominated by group SAR202 of Chloroflexi , candidate phylum Poribacteria and Acidobacteria , which was different in its composition from that obtained in clone libraries prepared form the same samples. Optimized assembly strategies allowed the reconstruction of full‐length rRNA sequences from the short ribo‐tags for more detailed phylogenetic studies of the dominant taxa. Cells of several phyla were visualized by FISH analyses for confirmation. Of the remaining 21 325 RNA‐tags, 10 023 were assigned to mRNA‐tags, based on similarities to genes in the databases. A wide range of putative functional gene transcripts from over 10 different phyla were identified among the bacterial mRNA‐tags. The most abundant mRNAs were those encoding key metabolic enzymes of nitrification from ammonia‐oxidizing archaea as well as candidate genes involved in related processes. Our analysis demonstrates the potential and limits of using a combined rRNA and mRNA approach to explore the microbial community profile, phylogenetic assignments and metabolic activities of a complex, but little explored microbial community.

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)